Mechanistic Aspects of the Formation of Adsorbable Organic Bromine during Chlorination of Bromide-containing Synthetic Waters. - Langsa, M.; Heitz, A.; Joll, Cynthia; von Gunten, U.; Allard, Sebastien (American Chemical Society, 2017)
During chlorination of bromide-containing waters, a significant formation of brominated disinfection byproducts is expected. This is of concern because Br-DBPs are generally more toxic than their chlorinated analogues. In this study, synthetic water samples containing dissolved organic matter (DOM) extracts and bromide were treated under various disinfection scenarios to elucidate the mechanisms of Br-DBP formation. The total concentration of Br-DBPs was measured as adsorbable organic bromine (AOBr). A portion of the bromine (HOBr) was found to react with DOM via electrophilic substitution (=40%), forming AOBr, and the remaining HOBr reacted with DOM via electron transfer with a reduction of HOBr to bromide (=60%). During chlorination, the released bromide is reoxidized (recycled) by chlorine to HOBr, leading to further electrophilic substitution of unaltered DOM sites and chlorinated DOM moieties. This leads to an almost complete bromine incorporation to DOM (=87%). The type of DOM (3.06 = SUVA254 = 4.85) is not affecting this process, as long as the bromine-reactive DOM sites are in excess and a sufficient chlorine exposure is achieved. When most reactive sites were consumed by chlorine, Cl-substituted functional groups (Cl-DOM) are reacting with HOBr by direct bromination leading to Br-Cl-DOM and by bromine substitution of chlorine leading to Br-DOM. The latter finding was supported by hexachlorobenzene as a model compound from which bromoform was formed during HOBr treatment. To better understand the experimental findings, a conceptual kinetic model allowing to assess the contribution of each AOBr pathway was developed. A simulation of distribution system conditions with a disinfectant residual of 1 mgC2 L(-1) showed complete conversion of Br(-) to AOBr, with about 10% of the AOBr formed through chlorine substitution by bromine.